(untitled) (Hekima Review, 2013)
Tertullian taught that baptism is indispensable for salvation because it imparts the grace that washes away our original sin and makes us capable of attaining a matured Christian life. By baptism, Tertullian was referring to the sacramental form of baptism that is done with water. From Tertullian, we observe that baptism by water was the acceptable practice in the early church. Today, there are lots of converts in Africa whom the Catholic Church does not confer the baptism of water and subsequently fails to admit them to her sacramental life because of their polygamous relations. This raises a question regarding the salvation of these polygamous families whom the church does not admit to the sacramental baptism. How do they receive baptismal grace and become part of the church? Added to this is the difficulty of pre-senting the concepts of grace and original sin in an African context. “The concepts of grace and Original Sin which constitute a vital element in this catechesis are not easy to understand. What does the Original Sin mean to an African?